Autonomous weapons in the light of the principles of international humanitarian law - حاتم, دعاء جليل; جعفر, محمود خليل (Journal of Legal Sciences, 2021)
This paper deals with "the prohibition of autonomous weapons in the light of the principles of international humanitarian law", The autonomous  weapon is the newly developed type of weapon, and it is the latest of the genius of the human race in finding another "automatic" race to undertake combat operations on its behalf, However, this matter was not left at all, Rather, each party to the armed conflict must abide by the principles of international humanitarian law to avoid the harmful effects of that weapon, In particular, adherence to the text of Article 36 of the First Additional Protocol of 1977, which obliges the Contracting Parties to conduct a review of their weapons before their launch to find out what is prohibited and permitted, This restriction, in addition to the other restrictions mentioned in the research, is considered a legal means that enables other countries to use it to restrict the manufacture, development and acquisition of this new weapon if it is inconsistent with international humanitarian law.